2021
DOI: 10.1002/advs.202101382
|View full text |Cite
|
Sign up to set email alerts
|

Construction of New Active Sites: Cu Substitution Enabled Surface Frustrated Lewis Pairs over Calcium Hydroxyapatite for CO2 Hydrogenation

Abstract: Calcium hydroxyphosphate, Ca 10 (PO 4 ) 6 (OH) 2 , is commonly known as hydroxyapatite (HAP). The acidic calcium and basic phosphate/hydroxide sites in HAP can be modified via isomorphous substitution of calcium and/or hydroxide ions to enable a cornucopia of catalyzed reactions. Herein, isomorphic substitution of Ca 2+ ions by Cu 2+ ions especially at very low levels of exchange created new analogs of molecular surface frustrated Lewis pairs (SFLPs) in Cu x Ca 10−x (PO 4 ) 6 (OH) 2 , thereby boosting its perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…11 Recently, the group of Ozin used copper substitution in calcium hydroxyapatite to design a CO 2 hydrogenation catalyst. 12 All these solid heterogeneous catalysts, however, do not take benefit from the mobility of a molecular partner in solution, which can greatly increase the chances of identifying novel FLPs systems. In this context, we wanted to investigate the possibility of creating a FLP in colloidal solutions based on inorganic nanoparticles of abundant first row transition metals (the Lewis acid) and an external ligand (the Lewis base), free to come and go from the nanoparticle's surface.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…11 Recently, the group of Ozin used copper substitution in calcium hydroxyapatite to design a CO 2 hydrogenation catalyst. 12 All these solid heterogeneous catalysts, however, do not take benefit from the mobility of a molecular partner in solution, which can greatly increase the chances of identifying novel FLPs systems. In this context, we wanted to investigate the possibility of creating a FLP in colloidal solutions based on inorganic nanoparticles of abundant first row transition metals (the Lewis acid) and an external ligand (the Lewis base), free to come and go from the nanoparticle's surface.…”
mentioning
confidence: 99%
“…11 Recently, the group of Ozin used copper substitution in calcium hydroxyapatite to design a CO 2 hydrogenation catalyst. 12 All of these solid heterogeneous catalysts, however, do not take benefit from the mobility of a molecular partner in solution, which can greatly increase the chances of identifying novel FLP systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The high-resolution XPS peaks for Ce-BiOBr exposed to a H 2 atmosphere at room temperature (Figure c,d) illustrate the slight movement to positive energy in the O 1s region, resulting from the formation of hydroxides due to the addition of H + , while the peaks of Ce 3d and Bi 4f show slight negative shifts, induced by the bonds of H – with Ce and Bi ions (Figure S17). These shifts could reflect the splitting of H 2 by the frustrated Lewis acid–base pair Ce 4+ -O 2– with protonation, evidently proving the FLP characteristics in Ce-BiOBr …”
Section: Resultsmentioning
confidence: 63%
“…The generation rates of CO and CH 4 over the BiOBr-OVs/C 3 N 4 heterojunction correspond to 13.8 and 6.1 μL h –1 , respectively, larger than that of the heterojunction C 3 N 4 /BiOBr without OVs . Our group reports that the products of CO 2 photoreduction for hollow BiOBr microspheres are dominated with CO and CH 4 in yields of 19.7 and 1.3 μL h –1 , showing 8.8 and 5.8 times as large as plate-like BiOBr, respectively . More recently, we showed that the PVP coordinated BiOBr has an excellent activity for CO 2 photoreduction with pure H 2 O under simulated sunlight.…”
Section: Introductionmentioning
confidence: 84%